(3GdeMGSf aj GdfXe hGdfKQs - (3CHh GdMSf fUQ Hf GdMSf GdeQZjGfjs
(3ChdgG (B:s
(3bGd GdTjN GdEeGe CHh GdMSf fUQ Hf GdMSf GdeQZjGfi QVi Gddg Yfg gPG cJGH CdafGg ai eMGSf GdcdGe dHYV ENhGffG ef GdQGZHjf ai GdCOH hGdefGaSjf ajg s
(3BNQgG (B:s
(3bO CHOY ai gPG GdHJ GdCNjQ hgPG GdMSf eG bjd ai gPG GdeYfi bGd UGMH jJjeg GdOgQ ai eMGSf Cgd GdYUQ hGdMeO ddg ChdkG hCNQkG hXGgQkG hHGWfkG hMSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3Cdag ai eMGSf GdcdGe heG jSJLGO ef UfGFYIs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(264/2) s
Keywords: (3GdHdGZIs